A Multi-channel Feature Combination Model for Ultra-short-term Wind Power Prediction Under Carbon Neutral Background - Shubang HUANG; Yao CHEN; Yuqing JIN (发电技术, 2021)
Wind power will become one of the dominant power sources of China oriented to carbon neutral. With the rapid development of artificial intelligence technology, artificial neural networks are widely used in wind power generation forecasting. Traditional artificial neural network algorithms use fixed-form data sets and simple network structures, which limits the overall expression ability and results in uncontrollable errors in ultra-short-term wind power forecasting due to various uncertain factors. In this work, a multi-channel feature combination model based on artificial neural network for ultra-short-term wind power prediction was proposed. Firstly, the data were reclassified and input into three neural networks to establish three feature combinations. After that, multi-channel features splicing and fusion were performed. The fused features were added to the fully connected neural network for power prediction, which can eliminate the interference between different features and effectively learn long-term dependent data features. Finally, the algorithm was verified on the actual data of five wind farms. The experimental results show that this method has better prediction accuracy than the single-channel model, and can improve the network stability.